Collocation in the Hadith of the Prophet, Hadiths of the Virtues of the Qur’an as a Model (Islamic Sciences Journal, 2023)
ABSTRACT                   Collocation is one of the methods that have an effect on the listener's soul, to which some of the beauties and aesthetics of speech are due because of the approximation of meanings. The Sunnah of the Prophet was full of this fine phenomenon, and it was abundant in the contexts of advice, counseling, education, enticing, and intimidation, so I preferred to present my research which is entitled (collocation in the hadith of the Prophet, hadiths of the virtues of the Qur’an as a model).   This analytical and  aesthetic reading has been conducted to reveal the rhetoric and good portrayal of the prophetic discourse, and its reflection on connotational, devotional and emotional sides. So I wanted to show some collocation meanings in examples of the hadiths of the Messenger   ( peace be upon him).